Retributivism, Consequentialism, and the Risk of Punishing the Innocent: The Troublesome Case of Proxy Crimes (Diametros, 2017)
This paper discusses differences between two major schools in philosophy of criminal law, retributivism and consequentialism, with regard to the risk of (unintentionally) punishing the innocent. As it is argued, the main point of departure between these two camps in this respect lies in their attitude towards the high evidentiary threshold in a criminal trial: while retributivism seems to strongly support setting this standard high, consequentialists may find it desirable to relax it in some cases. This discussion is set in the context of proxy criminalization, i.e. a situation, in which some suspicious behaviour (i.e. behaviour that is only in some correlation with wrongful conduct, while not being substantially wrongful in itself) is criminalized. Since proxy criminalization may be understood as an effective lowering of the evidentiary threshold, its employment is justifiable from the consequentialist perspective, while being highly problematic for the retributivists.